A NOVEL ALGORITHM BASED ON TRUST AUTHENTICATION MECHANISMS TO DETECT AND PREVENT MALICIOUS NODES IN MOBILE AD HOC NETWORK - Ngoc, Luong Thai; Tu, Vo Thanh (Journal of Computer Science and Cybernetics, 2018)
Ad hoc On-demand Distance Vector (AODV) routing protocol is one of the most popular reactive protocol used for Mobile Ad hoc Network, is target of many attack types. Some research works published related to improve of AODV based on digital signature, typical as SAODV and ARAN. However, they have some weakness, malicious can pass over security wall of SAODV by using fake keys, both of SAODV and ARAN can’t detect wormhole nodes in hide mode. In additions, detection solutions based on characteristics of attack types have proposed, they only bring about efficiency for each independent type of attack and malicious nodes can join to the discovered route by deliberately giving fake information concerning. This article proposes a trust authentication mechanisms (TAM) using public-key cryptograms RSA and digital certificates (DC) based on X509 standard. TAM allows a mobile node authenticates preceding nodes by checking control route packets through 3 steps: (1) Digital certificates; (2) actual neighbors; and (3) packet integrity authentications. Analysis results confirm that TAM can detect and prevent almost current routing protocol attack types, such as Blackhole/ Sinkhole, Grayhole, Flooding, Whirlwind and participation mode Wormhole attacks. Specially, the simulation results in NS2 show that TAM can detect and prevent successful to 100% malicious nodes using fake keys for all scenarios based on the number of UDP connections, 100% hide mode wormhole nodes for immobility scenarios and above 99% (the mistaken rate below 1.0%) for all mobility scenarios with 30m/s of maximum speeds and 1hop minimum tunnel length.